Sensomotoric Orthoses, Ankle–Foot Orthoses, and Children with Cerebral Palsy: The Bigger Picture - MacFarlane, Clare (Children (Basel), 2020)
Ankle–foot orthoses (AFOs) and sensomotoric orthoses (SMotOs) are two—clinically relevant, yet under researched—types of lower limb orthoses used in children with cerebral palsy (CP). Quality of life is a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity. Evaluating the effect of these two types of orthoses on quality of life in children with CP has not been reported on. The aim of this case study series was to synthesise and enrich the volume of evidence reported to inform real world applications of SMotO use in children with CP. Participants recruited were children with CP who performed the Berg Balance Scale, Timed Up-and-Go, the Gross Motor Function Measure and/or the Edinburgh Visual Gait Score in AFOs, SMotOs and barefoot where able. Qualitative data included videos of gait, a questionnaire and pedographs. Eight participants completed 39 quantitative and six qualitative measures, with the Edinburgh Visual Gait Score (EVGS) reporting the highest response. A general improvement was seen in gross motor skills and gait when wearing the SMotOs compared to AFOs and some parents reported that SMotOs were preferred. The reader is able to correlate the quantitative results with the qualitative evidence presented.